Wavelet toolware - Chui, Charles K.; Chan, Andrew K.; Liu, C. Steve (San Diego : Academic Press, 1998)
Designed as a learning and experimentation tool, not for solving high-precision computational problems.
System requirements : IBM PC or compatible, 32 MB RAM, Win32, color monitor, CD-ROM drive
Keywords: Wavelets (Mathematics)